2021
DOI: 10.1002/ca.23776
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between muscle size, obesity, body fat ratio, pain and disability in individuals with and without nonspecific low back pain

Abstract: Patients with nonspecific low back pain (NSLBP) may face motor control problems and health disability barriers during various tasks. However, studies investigating the extent of these disadvantages, and possible associated factors are quite limited in patients with NSLBP. To compare motor control performances and physical assessment domains between patients with NSLBP and asymptomatic controls. Twentyseven patients with NSBLP and 27 age-and sex-matched asymptomatic controls participated in this cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…A study conducted in 2021 by Uçar etal 25 Comparable study 16 was conducted in 2022 which analyzed the strategies for weight reduction and changes in anthropometric measures including BMI, waist, hip, waist to hip ratio and fat mass revealing the group which had high intensity training showed better results. This is similar to our study in which we found that resistance training group showed better results.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2021 by Uçar etal 25 Comparable study 16 was conducted in 2022 which analyzed the strategies for weight reduction and changes in anthropometric measures including BMI, waist, hip, waist to hip ratio and fat mass revealing the group which had high intensity training showed better results. This is similar to our study in which we found that resistance training group showed better results.…”
Section: Discussionmentioning
confidence: 99%
“…retrospectively demonstrated that young patients experiencing unilateral neurological symptoms due to LDH might be at a higher risk of developing LBP if they exhibit symmetrical atrophy of the bilateral MF [ 155 ]. Two cross-sectional studies suggested that morphological changes in the paraspinal muscles might lead to different clinical presentations [ 26 , 156 ]. The degree and manifestation of pain might be influenced by the escalation of disability and functional impairment as potential determinants [ 156 ].…”
Section: Paraspinal Muscles and Thoracic/lumbar Disordersmentioning
confidence: 99%
“…5 Low back pain (LBP) (i.e., acute or chronic pain in the lumbar or sacral regions) is one of the most common musculoskeletal disorders that lead to inactivity, postural disorders, and muscle dysfunctions, which can result in disability, reduced quality of life and loss of productivity at work. 6 In rural workers, LBP is the most commonly reported complaint, having significant consequences on both the clinical and economic status of these individuals. 7 There is an increasing prevalence of LBP in Brazil, which has shown a 79% increase in the total number of years lived with disability since 1990.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to workers from other economic sectors, rural workers demonstrate greater exposure to LBP's risk factors, 7 and have a longer time off work due to LBP, 8 since work in the countryside consists of strenuous tasks and many manual demands, 11 such as exposure to vibrations; trunk flexion and rotational movements performed repeatedly; and lifting/carrying high loads at heights above the shoulder joint. 6,10 The presence of LBP contributes to physical inactivity and decreased muscle mass and strength. 12 The lack of physical activities contributes to the development of obesity, which is considered public health trouble.…”
Section: Introductionmentioning
confidence: 99%